The Reaction of Some Mung Bean (Vigna radiata Wilczek) Genotypes with Meloidogyne incognita Race 2 - Fatma Gül GÖZE ÖZDEMİR; Ruziye KARAMAN (Türkiye Tarımsal Araştırmalar Dergisi, 2020)
In this study, it was aimed to determine the reactions and host states of different mung bean (Vigna radiata Wilczek) genotypes, collected from different regions of Turkey, with Meloidogyne incognita race 2. For this purpose, 14 different mung bean genotypes and one registered variety were used in the study. The evaluation process was made according to 1-9 root gall scale and the egg package production rate scale, and resistance index was calculated. As a result of the study, a high level of resistance in 1 genotype, 1 moderate resistance, 2 intermediate hosts, 2 very susceptible, 5 medium susceptible, and 4 susceptible reactions were detected against M. incognita race 2. In the genotype named 50 N 01 with high resistance, the gall index was 1.4, the egg mass production rate was 1.8, and the resistance index was 6.4, while the gall index was 3.4, the egg mass production rate was 4.4 and the resistance index was 31.4 in the genotype named 30 Ç 01. According to the study results, the genotypes 30 Ç 01 and 50 N 01 could be used as a parent in hybridization studies to develop resistant varieties against M. incognita.